Sources of Academic Stress: Stress Management among regular and executive MBA Students - Moula Bakhsh, Maryam; Sayed, Sayeeda Amber (International Journal of Endorsing Health Science Research, 2015)
Background Stress is the wear and tear a human body experience in order to adjust to the continually changing environment. However, too much stress affects health, productivity and relationships. There is increase recognition of stress in academic literature. Stress is basically an emotional imbalance incurred due to multiple reasons e.g. test, projects, paper competitive nature within your chosen field, future projects prospects and financial worries about school. Study Design Cross Sectional Study Survey Size Surveying 100 of Regular and Executive MBA students Survey Side Business Institute of Karachi Duration Four months from Sep to Dec 2014 Sampling Technique Random Sampling Technique Statistical Analysis Include Frequency, Mean±SD and Chi Square Statistical Analysis Tools EpiData, SPSS and Excel Main Outcome Measure Stressors and Stress Management Result Data were collected using Random sampling techniques from 100 participants through a cross sectional survey. The significant stressors reported were pressure due to vastness of curriculum, numerous assignments and dissatisfaction with the class lectures. Major stress reactions were found to be pressure trembling, crying and excessive smoking. Coping strategies were organizing and prioritizing task, getting enough sleep and even taking antidepressants. Conclusion This study provides an insight for initiating efforts to reduce the intensity of academic stress and work out of counseling trial to aid in the sound progression of students’ mind and bodies.